2014
DOI: 10.1002/mrd.22316
|View full text |Cite
|
Sign up to set email alerts
|

Bovine embryo survival under oxidative‐stress conditions is associated with activity of the NRF2‐mediated oxidative‐stress‐response pathway

Abstract: In present study, we sought to examine the ability of preimplantation bovine embryos to activate the NF-E2-related factor 2 (NRF2)-mediated oxidative-stress response under an oxidative stress environment. In vitro 2-, 4-, 8-, 16-cell-, and blastocyst-stage embryos were cultured under low (5%) or high (20%) oxygen levels. The expression of NRF2, KEAP1 (NRF2 inhibitor), antioxidants downstream of NRF2, and genes associated with embryo metabolism were analyzed between the embryo groups using real-time quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 112 publications
6
94
0
3
Order By: Relevance
“…Accordingly, the maturation and fertilization were done at high oxygen tension in the current study. Furthermore, here we showed that irrespective of the sex of embryo, those embryos cultured under 5% oxygen level showed higher development rate of blastocyst than those under 20% oxygen level, as it has been reported before (Amin et al, ; Leite et al, ). Differences in metabolism (Gómez et al, ) and genetics (Bermejo‐Alvarez et al, ) between male and female bovine embryo could contribute to skewness in sex ratio of the resulted embryos (Oliveira et al, ; Xu, Yadav, King, & Betteridge, ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Accordingly, the maturation and fertilization were done at high oxygen tension in the current study. Furthermore, here we showed that irrespective of the sex of embryo, those embryos cultured under 5% oxygen level showed higher development rate of blastocyst than those under 20% oxygen level, as it has been reported before (Amin et al, ; Leite et al, ). Differences in metabolism (Gómez et al, ) and genetics (Bermejo‐Alvarez et al, ) between male and female bovine embryo could contribute to skewness in sex ratio of the resulted embryos (Oliveira et al, ; Xu, Yadav, King, & Betteridge, ).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, our results showed that the blastocyst rate at Days 7 and 8 (Figure ) were skewed toward the male embryos when cultured under either 5 or 20% oxygen levels. As it was been reported previously (Amin et al, ; Leite et al, ; Yoon et al, ), embryos cultured under higher oxygen tension (20%) revealed elevated intracellular ROS accumulation irrespective of the sex of the embryos (Figure ). However, male embryos exhibited higher ROS accumulation than female embryos at lower oxygen level, which may be attributed to higher metabolism rate of male embryo compared with female counterparts (Tiffin, Rieger, Betteridge, Yadav, & King, ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The role of NFE2L2 has been investigated in a different cultural environment in bovine embryos that reached blastocyst stage (Gad et al, 2012). However, under suboptimal culture condition in early bovine embryos, NFE2L2-KEAP1 signaling pathway protects the embryo from oxidative stress (Amin et al, 2014). But also, the development of rabbit embryo was promoted by activation of NFE2L2 during induced oxidative stress condition (Mehaisen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%